Mineral systems approach applied to prospectivity mapping of lithium related to peraluminous magmatism in southern Peru - Marchena Campos, Alonso Arturo (2024)
We apply the mineral systems (MS) approach to generate lithium (Li) prospectivity maps in southem Peru by integrating geological data using artificial intelligence (Al). Our method identifies critica! processes and key elements for the formation of Li deposits, providing a picture more complete than traditional approaches. The results highlight promising new Li areas in addition to the known mineralized metallogenic belts, promoting broader opportunities. Our method uses random forest algorithms and neural networks, and results in predictive maps. We however highlight the need for improved geological and geochemical data and thus recommend more detailed local research. Our approach provides an effective tool for mineral exploration, highlighting the importance of a comprehensive, systemic approach to mineral resource identification.